INFORMATION SYSTEMS DESIGN SERVICES DENTAL CLINIC PATIENTS - Kosdiana Kosdiana (JAKSTIK Journal, 2006)
The use of computer technology at the present time is very much needed in data management both in the number of large and small. Because in addition can also save time and effort to minimize errors that occur if done manually. Here on the system design of patient care dental clinic needed a computerized system that can support operational services to society as a maximum, and it can become more effective and efficiency.Â  In order for data to be processed more easily, quickly, precisely and accurately.